SARS-CoV-2 Papain-like Protease Responsive ZnO/Daclatasvir-Loaded Chitosan/Gelatin Nanofibers as Smart Antimicrobial Medical Textiles: In Silico, In Vitro and Cell Studies - Mohamed Hamdi; Akram M. Elkashlan; Mohamed A. Hammad; Isra H. Ali (MDPI AG, 2023)
A significant number of deaths are reported annually worldwide due to microbial and viral infections. The development of protective medical textiles for patients and healthcare professionals has attracted many researchers' attention. Therefore, this study aims to develop smart drug-eluting nanofibrous matrices to be used as a basic material for medical textile fabrication. First, chitosan/gelatin nanofibers were selected as the basic material owing to the wide antimicrobial activity of chitosan and the capability of gelatin to be hydrolyzed in the abundance of the papain-like protease (PLpro) enzyme secreted by SARS-CoV-2. Daclatasvir (DAC), an NS5A inhibitor, was selected as the model drug based on in silico studies where it showed high anti-SARS-CoV-2 potential compared to FDA-approved references. Due to their reported antimicrobial and antiviral activities, ZnO NPs were successfully prepared and incorporated with daclatasvir in chitosan/gelatin nanofibrous matrices through electrospinning. Afterward, an in vitro release study in a simulated buffer revealed the controlled release of DAC over 21 days from the nanofibers compared to only 6 h for free DAC. On the other hand, the abundance of PLpro induced the complete release of DAC from the nanofibers in only 4-8 h. Finally, the nanofibers demonstrated a wide antimicrobial activity against S. aureus, E. coli, and C. albicans.